Faktor-Faktor yang Mempengaruhi Profitabilitas Bank Muamalat di Indonesia - Yuwita Ariessa Pravasanti; Wikan Budi Utami (ITB AAS INDONESIA Surakarta, 2020)
This study aims to obtain empirical evidence related to the influence of Indonesian Muamalat bank profitability. Characteristics of the influence of wadi'ah demand deposits, wadi’ah savings and mudharabah savings. This study uses secondary data with quarterly financial data population of PT. Bank Muamalat Indonesia from 2011 to 2018. The sampling technique uses quarterly financial data of PT. Bank Muamalat Indonesia has 32 data. The analytical tool used is multiple regression analysis. The results showed that the wadi'ah giro variable partially had a significant effect on profit / ROA. Show that t count is 2,356 ≥ t table is 1,699 while the value of Sig. t 0.026 ≤ Sig.α 0.05. Wadi'ah savings variable partially has a significant effect on profit / ROA. Shows that t count is - 3,135 ≤ t table is 1,699 while Sig. 0.004 ≤ α 0.05. Mudharabah savings variable partially has a significant effect on profit / ROA. Shows that t arithmetic of - 0.334 ≤ t table of 1.699 while the value of Sig. α 0.741 ≥ 0.05, then Ho is rejected and H1 is accepted. The results showed that multiple regression analysis obtained the coefficient of determination (R2) was 0.412 or equal to 41.2%. This means that Wadi'ah Giro, Wadi'ah Savings and Mudharabah Savings jointly affect bank profitability.